PENGARUH PROMOTION, PRICE PERCEPTION DAN EXPERIENCE TERHADAP CUSTOMER LOYALTY DENGAN SATISFACTION DAN TRUST SEBAGAI VARIABEL INTERVENING - Masytohannum Nasution; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (SEGMEN: Jurnal Manajemen dan Bisnis, 2022)
This study aims to examine the "Effect of Promotion, Price Perception and Experience on Loyalty with Satisfaction and Trust as Intervening Variables".The sample of this study was 140 Shopee users in Yogyakarta using questionnaires which were distributed using purposive sampling technique. The research results show (1) there is a positive and significant effect of promotion on satisfaction, (2) there is a positive and significant effect of price perception on satisfaction, (3) there is a positive and significant effect of experience on trust, (4) there is a positive and significant effect on satisfaction with loyalty, (5) There is a positive and significant effect of trust on loyalty, (6) there is a positive and significant influence of promotion on loyalty through satisfaction, (7) there is a positive and significant effect on perception towards loyalty through satisfaction, and (8) there is a positive and significant influence of experience on loyalty through trust from Shopee users in Yogyakarta.Keywords : Promotion, Price Perception, Experience, Satisfaction, Trust, Customer Loyalty